Evaluation of essential oil extracted from ginger, cinnamon and lemon for therapeutic and biological activities. (September 2022) - Rasool, Nazia; Saeed, Zohaib; Pervaiz, Muhammad; Ali, Faisal; Younas, Umer; Bashir, Rashida; Bukhari, Syed Majid; Mahmood khan, Rana Rashad; Jelani, Seemal; Sikandar, Rizwan
Abstract: Essential oil extracted from plants has many applications in the field of medicine, cosmetic and pharmaceuticals due to cost effectiveness and therapeutic effects associated. In this article, we have compiled discussion on the essential oil extracted from ginger, cinnamon, and lemon leaves. Essential oils are rich source of antioxidant compounds like cinnamaldehyde, zingiberene and limonene. This review article covers the literature related to antioxidant and biological activities of essential oils extracted from ginger, cinnamon and lemon. In addition, applications of the essential oils in the field of medical, pharmacology, cosmetic etc, have been discussed. Role of essential oils, for anti-cancer, anti-hypertension, reduction of heart diseases and maintaining of blood circulation and digestion due to presence of antioxidant components, has been discussed. Literature has also supported Covid-19 preventive effects of essential oils. Keeping in view the positive effects on health, essential oils can be used as supplements. Furthermore, essential oils must be further investigated for their biological activities followed by development of essential oil based drugs and pharmaceutics. Highlights: Utilization in field of medicine, cosmetic and pharmaceuticals. Essential oil is full of antioxidant compounds and rich of antioxidant compounds like cinnamaldehyde, zingiberene and limonene. Role zingiberene, cinnamaldehyde and limonene illustrated in term of antioxidant and other biological activity.